Sequential EGFR mutation and ALK rearrangement in adenocarcinoma lung, with rare metastasis to bilateral breast, ovary and endometrium. (2019) - Anjali, V.R.; Pandey, Rambha; Srivastava, Astha; Rajeshwari, Madhu; Pandey, Durgatosh; Sharma, M.C.
Abstract: With the advent of targeted therapies there was a paradigm shift in the treatment of metastatic adenocarcinoma of lung. Immuno-histopathology and molecular subtyping in metastatic adenocarcinoma lung have enabled personalized treatment for each patient. Oncogenic driver mutations in non-small cell lung cancer are commonly EGFR (Epidermal Growth Factor Receptor) gene mutation and ALK (Anaplastic Lymphoma Kinase) gene rearrangement, which are mutually exclusive. Almost 60–64% patients have oncogenic mutation, which are mutually exclusive. Here, we present a case with EGFR mutation and ALK gene rearrangement which was expressed sequentially and with metastasis to rarest sites bilateral breast, ovaries and endometrium. Even though presented with upfront metastatic disease, patient was treated with multiple lines of targeted agents, by which patient survived for 5 years with good quality of life.